IbM WARUNG WISATA SELOREJO: PENINGKATAN KEMAMPUAN PENGELOLA UMKM WARUNG SELOREJO DALAM TATAKELOLA KEUANGAN, PEMASARAN DAN PELAYANAN KONSUMEN - Ernani Hadiyati; Dwi Orbaningsih; Sugeng Mulyono (SHARE: Journal of Service Learning, 2015)
This community service project aims to improve the managerial performance of SMEs on accounting, marketing and services to their consumers. This objective is achieved through brushing up the managerial skills of the manager of the targeted SMEs, especially the financial and marketing skills, as well as their performance in providing consumer services. The expected outcomes are: SMEs’ managerial training, module and guidelines for applying accounting principles and providing good consumer services. The method used is the combination of common training principles, assistance and financial support for encouraging the targetted SMEs to implement the materials used in the training. The result of this project indicates that the targeted SMEs, that is, Selorejo tourists’ food stall, show improvement in their performance in accounting and consumer service.